Identifikasi Nilai Budaya Masyarakat Sungai Jelai Basirih Selatan Sebagai Sumber Belajar IPS - Muhammad Adhitya Hidayat Putra; Muhammad Rezky Noor Handy; Bambang Subiyakto; Rusmaniah Rusmaniah; Norhayati Norhayati (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2022)
Meaningful social studies learning needs to be explored through the culture surrounding students. The Sungai Jelai Basirih Selatan community has cultural values that are important as a source of social studies learning. The purpose of this article is to identify the cultural values that exist in the Sungai Jelai Basirih Selatan community and the contribution of these cultural values as a source of social studies learning. The method used was a qualitative approach. To collect the data, this research used observations, interviews, and documentation. To analyze the data, this research used the Miles and Huberman model, namely data reduction, data presentation, and data verification, while the validity of the data used triangulation. The results showed that identifying cultural values in the Sungai Jelai Basirih Selatan community was related to the pattern of daily community relations that had positive values. These values consist of religious values, hard work values, and mutual cooperation values. The various values obtained are integrated into teaching materials as social studies learning resources. Keywords: Society, values, and sources of social studies learning.